2018
DOI: 10.1155/2018/1714896
|View full text |Cite
|
Sign up to set email alerts
|

VDR Agonist Prevents Diabetic Endothelial Dysfunction through Inhibition of Prolyl Isomerase‐1‐Mediated Mitochondrial Oxidative Stress and Inflammation

Abstract: Background and aim Upregulation of prolyl isomerase-1 (Pin1) protein expression and activity was associated with the pathogenesis of diabetic vasculopathy through induction of endothelial oxidative stress and inflammation. Moreover, VDR agonist protects against high glucose-induced endothelial apoptosis through the inhibition of oxidative stress. We aimed to explore the effects of the VDR agonist on diabetes-associated endothelial dysfunction and the role of Pin1 in this process. Methods Streptozocin-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Since the identification of the importance of human peptidyl-prolyl cis/trans isomerase Pin1 in Alzheimer’s disease [104] through the modulation of Tau protein [45], Pin1 and juglone have gained considerable attention. As a result, and largely through studies using juglone, Pin1 has also been implicated in a wide variety of clinical conditions including immune response [105], allergy [106], cancer [107,108], hyperparathyroidism [109], rheumatoid arthritis [110], vascular pathology [111,112,113,114,115], diabetes [116], Parkinson’s disease [117], and cardiac fibrosis [118,119,120]. There are numerous review articles already available on Pin1, and thus interested readers should refer to these articles that are found in PubMed and other sources.…”
Section: Role Of Juglone As An Inhibitor Of Peptidyl-prolyl Cis/trmentioning
confidence: 99%
“…Since the identification of the importance of human peptidyl-prolyl cis/trans isomerase Pin1 in Alzheimer’s disease [104] through the modulation of Tau protein [45], Pin1 and juglone have gained considerable attention. As a result, and largely through studies using juglone, Pin1 has also been implicated in a wide variety of clinical conditions including immune response [105], allergy [106], cancer [107,108], hyperparathyroidism [109], rheumatoid arthritis [110], vascular pathology [111,112,113,114,115], diabetes [116], Parkinson’s disease [117], and cardiac fibrosis [118,119,120]. There are numerous review articles already available on Pin1, and thus interested readers should refer to these articles that are found in PubMed and other sources.…”
Section: Role Of Juglone As An Inhibitor Of Peptidyl-prolyl Cis/trmentioning
confidence: 99%
“…VDR was the nuclear receptor for the biologically most active vitamin D metabolite 1α,25-dihydroxyvitamin D3, which not only exerted a significant role in the metabolism and homeostasis of calcium and phosphate, but also involved in the process of cellular proliferation and differentiation, anti-inflammatory and anti-oxidative function [14,[35][36][37][38]. Increasing evidences indicated that VDR played an important function in the process of COPD during the past few decades [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that upregulation of Pin1 expression is associated with mitochondrial reactive oxygen species production and mitochondrial damage through interaction with the phosphorylated adaptor protein p66Shc and endothelial nitric oxide synthase. This then leads to endothelial dysfunction and vascular inflammation [ 7 9 ]. Additionally, the Pin1 inhibitor juglone is effective in inhibiting diabetic vascular lesions [ 10 ], which is a brown dye isolated from the shell and leaves of the walnut tree [ 11 ].…”
Section: Introductionmentioning
confidence: 99%